A Third Millennium Stone Plaque from Gird Maiwizha (Rania Plain, Iraqi Kurdistan) - Eidem, Jesper; Coppini, Costanza (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
The article presents a remarkable new find from a site on the west edge of the Rania Plain (Iraqi Kurdistan) in its iconographic, archaeological, and historical context.